Warli: A Pedagogical Tool for Primary Classes - Sharma, Ridhi (THE PRIMARY TEACHER, 2019)
India is known for its rich diversity as it is home to different religions, cultures, languages and art forms. Art plays a very important role in a child’s life. It helps a child to develop motor skills (both fine and gross), appreciates numeracy, reduces stress, builds a child’s self-esteem, enhances creativity and can also act as a medium for starting a conversation. Integrating various Art forms with school subjects helps to facilitate specific skill development and holistic funbased learning among students. This is especially true in primary classes where an interdisciplinary approach is followed in order to build a foundation for later classes. This article focuses on how integrating such Indian Art form known as warli can lead to better conceptual clarity among students in different subjects.